BMAL1 attenuates intervertebral disc degeneration by activating the SIRT1/PGC-1α pathway: evidence from vitro studies - Peiming Sang; Yanyan Ma; Xie Zhang; Binhui Chen; Fan He; Neng Shen; Jiangang Zhao (Scientific Reports)
Abstract To explore the potential effects and the corresponding mechanisms of brain and muscle arnt-like protein-1 (BMAL1) on the progression of intervertebral disc degeneration (IVDD) in vitro studies. The expression of BMAL1, SIRT1 and PINK1 were evaluated by the method of siRNA/pcDNA in the immortalized nucleus pulposus (NP) cells. The expression of SIRT1/PGC-1α pathway was assessed. The characteristics of NP cell, containing the activity and density, the level of apoptosis, inflammatory response, reactive oxygen species (ROS), senescence, and mitophagy were evaluated. The overexpression of BMAL1 was achieved with the pcDNA3.1, the expression of SIRT1 and PGC-1α were increased, the inflammatory response, the ROS, the level of apoptosis and senescence were decreased, however, the level of mitophagy, the activity and density of NP cell were enhanced. The BMAL1 inhibites the progression of IVDD by activating the SIRT1/PGC-1α pathway in the vitro studies.